2020
DOI: 10.1016/j.heliyon.2020.e04928
|View full text |Cite|
|
Sign up to set email alerts
|

One-pot hydrothermal synthesis of a magnetic hydroxyapatite nanocomposite for MR imaging and pH-Sensitive drug delivery applications

Abstract: Synthetic hydroxyapatite (HA) due to its high biocompatibility, anti-inflammatory properties, high stability, and a flexible structure in combination with magnetic nanoparticles has the strong potential to be used in modern medicine including tissue engineering, imaging, and drug delivery. Herein, a hydrothermal process was used to prepare magnetite nanoparticles dispersed on the hydroxyapatite nanorods with cetyltrimethylammonium bromide (CTAB) as a surfactant. Characterization study of the synthesized iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The rod-shaped structure of the apatitic material can be noticed, as presented by our group [6,13] and other authors for metal-substituted hydroxyapatite [38], as well as the presence of the smaller, quasi-spherical magnetic phase. The overall morphology of the composite is similar to the one reported by Kermanian et al [39] for magnetite nanoparticles dispersed on hydroxyapatite nanorods. Given the identified morphologies on the TEM images, it is most likely that the pararobertsite phase also has a rod-shaped structure, but this aspect remains to be fully elucidated.…”
Section: Analytical Characterization Of the Materialssupporting
confidence: 84%
“…The rod-shaped structure of the apatitic material can be noticed, as presented by our group [6,13] and other authors for metal-substituted hydroxyapatite [38], as well as the presence of the smaller, quasi-spherical magnetic phase. The overall morphology of the composite is similar to the one reported by Kermanian et al [39] for magnetite nanoparticles dispersed on hydroxyapatite nanorods. Given the identified morphologies on the TEM images, it is most likely that the pararobertsite phase also has a rod-shaped structure, but this aspect remains to be fully elucidated.…”
Section: Analytical Characterization Of the Materialssupporting
confidence: 84%
“… 48 The discovery of novel agents which sensitize malignant cells to the effect of radiation would increase tumor response by slowing dividing tumors sensitive to irradiation while minimizing toxicity to the surrounding organs by lowering the effective therapeutic dose. 49 , 50 In this regard, the role of QMNPs to enhance the radiosensitivity of MCF-7 cancer cells was evaluated. The current data of the in vitro study revealed that QMNPs enhanced the suppression of MCF-7 cancer cells proliferation as examined qualitatively by MTT assay and inverted light microscope, compared with the sole RT treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although the magnetic nanoparticles have low toxicity and their biologically compatible (Yang, Gong, and Zhang, 2010), the aggregation process makes magnetite nanoparticles difficult to internalized to plant cell (Dağlioğlu and Yilmaz, 2018). Hydroxyapatite particles is the best inorganic auxiliary material that prevent aggregation of Fe 3 O 4 (Kermanian, Naghibi, and Sadighian, 2020). However, the chlorophyll content of aged leaves treated with magnetite-hydroxyapatite nanocomposite have shown an opposite tendency compared to treated with magnetite nanoparticles.…”
Section: Chlorophyll Content Of Wheatmentioning
confidence: 99%